Disaggregated Survey Data on Taxation to Improve Policy Design : A Perspective from the Ethiopia Socioeconomic Survey (2018/19) - Ambel, Alemayehu A.; Komatsu, Hitomi; Koolwal, Gayatri; Tsegay, Asmelash H.; Yonis, Manex B. (World Bank, Washington, DC, 2021)
A disaggregated analysis of the tax burdens and economic needs of the most economically vulnerable - such as poor women and men, informal workers, and owners of micro- and small enterprises - is crucial for designing equitable and well-targeted tax and public spending policies. This is particularly important in low-income countries, where formal and informal tax systems often exist in parallel, and administrative data is sparse. Availability of data on tax payments by households and non-farm enterprises, individual-level employment and asset ownership, and contributions to community institutions and infrastructure programs can reveal important distributional implications for tax policy design going forward. This survey brief summarizes findings from the tax module of the nationally representative 2018-19 Ethiopia socioeconomic survey (ESS). The tax module covers different types of formal and informal taxes that households, businesses, and individuals pay, as well as informal contributions towards services and infrastructural improvements in the community. Findings from the multi-topic survey also reveal different tax burdens by socioeconomic and demographic groups, as well as across rural and urban areas, that are important for national tax policy design and targeting.